Salivary glands associated with polyethism in the termite Cornitermes cumulans (Isoptera, Termitidae, Syntermitinae) - Costa-Leonardo, Ana Maria [UNESP]; Janei, Vanelize [UNESP]; da Silva, Iago Bueno [UNESP] (Springer Nature, 2025)
The salivary glands of termite workers are acinar and multifunctional organs, with a role in construction, defense, and digestive processes, besides pheromone production. The acini comprise central and peripheral cells, also known as parietal cells. Aiming to understand the contribution of parietal cells to the saliva of termite workers and soldiers, a caste primarily engaged in defense, we compared the occurrence and morphology of these cells in both castes of Cornitermes cumulans. To do so, salivary acini from workers and soldiers of this species were fixed and processed for morphometry, histology, and transmission electron microscopy. The acinar area varied between castes in terms of the superficial area, being larger in workers. In both castes, the parietal cells are triangular and smaller than the central ones. They occur in pairs in the periphery of the acini and are always surrounded by well-developed microvilli. The most important morphological feature of these cells is the presence of many secretory vesicles, which are electron-lucent in workers and electron-dense in soldiers. Such cellular features suggest different saliva production and composition, reflecting the polyethism in C. cumulans, as the salivary glands are directly involved in distinct tasks performed by workers and soldiers.